Process simulation of an efficient temperature swing adsorption concept for biogas upgrading. (1st November 2018) - Vogtenhuber, H.; Hofmann, R.; Helminger, F.; Schöny, G.
Abstract: In this work, a simulation tool for an integrated temperature swing adsorption (TSA) carbondioxide ( CO 2 ) capture process is introduced and used to study the feasibility of the process for biogas upgrading applications. The TSA process consists of interconnected multi-stage fluidized bed columns and utilizes solid amine sorbents for selective adsorption of CO 2 . The simulation tool has been developed in the process simulation software IPSEpro™ and performs mass- and energy balance calculations that are based on a suitable adsorption equilibrium model. Changes of the adsorbent CO 2 loadings and the corresponding heating or cooling requirements are calculated for the individual fluidized bed stages of the adsorber and desorber column. The adsorption equilibrium calculations have been performed, using a Langmuir model that was fitted to CO 2 adsorption data of an amine functionalized solid sorbent material. Within this work, the qualitative impact of the regeneration temperature and the stripping gas feeding rate on the overall process performance has been studied. Furthermore, the feasibility for integration of a high temperature compression heat pump (HP) has been assessed. The HP recovers heat from the adsorber to drive adsorbent regeneration within the desorber. Results obtained from this work clearly indicate a great potential of the multi-stage fluidized bed TSA process for biogas upgrading, especially in combination with the proposed heat pump configuration. Highlights: Innovative temperature swing adsorption model for biogas upgrading. Simulation of a fully continuous fluidized bed TSA process. Energy results of the proposed TSA process for biogas upgrading in terms of active cooling/heating and electricity supply. Integrated heat pump concept enables potential energy efficiency.